2018
DOI: 10.1177/0269215517745348
|View full text |Cite
|
Sign up to set email alerts
|

A mixed treatment comparison on efficacy and safety of treatments for spasticity caused by multiple sclerosis: a systematic review and network meta-analysis

Abstract: We recommended botulinum toxin as the optimal intervention for multiple sclerosis-related spasticity. Cannabinoids and transcutaneous electric nerve stimulation could also be considered as multiple sclerosis-related spasticity treatments but their safety remained to be verified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…Research of oral BZs in spasticity is mixed and insufficient [68][69][70][71], however, and when benefit was seen, comparison trials favored other agents for functional and tolerability reasons [68,[72][73][74][75][76]. In a metaanalysis of 23 trials (total N = 2720), diazepam was not recommended for spasticity in multiple sclerosis because of side effects and greater efficacy found with cannabinoids, botulinum toxin, and transcutaneous electrical stimulation [77]. Note that spasticity trials were not designed to examine pain endpoints so no firm conclusions can be drawn about analgesic efficacy [71].…”
Section: Benzodiazepine Use For Analgesiamentioning
confidence: 99%
“…Research of oral BZs in spasticity is mixed and insufficient [68][69][70][71], however, and when benefit was seen, comparison trials favored other agents for functional and tolerability reasons [68,[72][73][74][75][76]. In a metaanalysis of 23 trials (total N = 2720), diazepam was not recommended for spasticity in multiple sclerosis because of side effects and greater efficacy found with cannabinoids, botulinum toxin, and transcutaneous electrical stimulation [77]. Note that spasticity trials were not designed to examine pain endpoints so no firm conclusions can be drawn about analgesic efficacy [71].…”
Section: Benzodiazepine Use For Analgesiamentioning
confidence: 99%
“…BTX-A has long been used in the symptomatic treatment of MS patients, such as for a hyperactive bladder [46]. Likewise, studies and reviews [47][48][49] have reported BTX-A use for the treatment of spasticity, but few randomised trials have been performed. In this regard, the review by Dressler et al 2017 [49] found only three RCTs [50][51][52], and a recent Italian consensus on spasticity treatment considered only 4 trials concerning BTX [53].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Among BTX-A formulations, aboBTX-A and onaBTX-A were predominantly injected to treat spasticity, apart from in one study with mixed samples that used incoBTX-A [39] neurotoxin. All studies showed a significant efficacy of BTX in reducing spasticity due to MS [47][48][49]. BTX-A dosages up to 2000 UI for Dysport [56,57] and up to 400 UI for Botox were injected without significant side effects.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…This phenomenon translates into BoNTs being an effective treatment for a variety of movement disorders and other neurological and non-neurological conditions. Several studies have indicated its effectiveness in the treatment of disorders such as dystonia, post stroke spasticity, and cerebral palsy to name a few [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The side effect profile of long-term botulinum toxin injections has been well documented, especially in individuals with dystonia and spasticity [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated its effectiveness in the treatment of disorders such as dystonia, post stroke spasticity, and cerebral palsy to name a few [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The side effect profile of long-term botulinum toxin injections has been well documented, especially in individuals with dystonia and spasticity [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. A retrospective longitudinal descriptive analysis by Ramirez-Castenada et al of 89 subjects with dystonia showed that the most common side effects were dysphagia, ptosis, and neck weakness which has been duplicated in several other studies [ 3 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%